Job Design Theory: School Structure, Teachers' Job Characteristics and Microeconomic Resource Allocation in Classrooms - Bettye MacPhail-Wilcox; Julia I. Dreyden (Educational Considerations, 1992)
The results of this exploratory study of job design in education are encouraging.